Pakistan, politics and political business cycles - Irem Batool; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2009)
This paper studies whether in Pakistan the dynamic behavior of unemployment, inflation, budget deficit and real GDP growth is systematically affected by the timing of elections. We cover the period from 1973-2009. Our results can be summarized as follows: 1. Unemployment tends to be lower in pre-election periods and tends to increase immediately after elections, perhaps as a result of politically motivated employment schemes. 2. In ation tend to be lower in preelection periods, perhaps as a result of pre-electoral price regulation. 3. We find election year increases in the governmental budget deficit, financed by heavy government borrowings from the central bank and banking sector. 4. Real GDP growth and real governmental investment growth declines during pre and post election terms.
Keywords: D72; D78; H50; H61; E51; 330; Opportunistic Political Business Cycle; Fiscal Policy; Macroeconomics; Elections; Asia; Pakistan